2009
DOI: 10.1038/onc.2009.253
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic tumor–stroma crosstalk guides epithelial to mesenchymal transition at the tumor edge

Abstract: The tumor-stroma crosstalk is a dynamic process fundamental in tumor development. In hepatocellular carcinoma (HCC), the progression of malignant hepatocytes frequently depends on transforming growth factor (TGF)-b provided by stromal cells. TGF-b induces an epithelial to mesenchymal transition (EMT) of oncogenic Ras-transformed hepatocytes and an upregulation of platelet-derived growth factor (PDGF) signaling. To analyse the influence of the hepatic tumor-stroma crosstalk onto tumor growth and progression, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(98 citation statements)
references
References 56 publications
(72 reference statements)
4
92
0
Order By: Relevance
“…A TGF-b inhibitor inhibits tumorosphere formation by murine breast cancers and also tumor growth and metastasis (Bandyopadhyay et al, 2010). The EMT-inducing effect of TGF-b is mediated in transformed hepatocytes by the induction of growth factors in stromal myofibroblasts, which themselves cause EMT (van Zijl et al, 2009). In the RAS-RAF pathway, extracellular signal-regulated kinase 2 (ERK2) would specifically be involved in EMT induction but not ERK1 (Shin et al, 2010).…”
Section: Cancer Cells S Floor Et Almentioning
confidence: 99%
“…A TGF-b inhibitor inhibits tumorosphere formation by murine breast cancers and also tumor growth and metastasis (Bandyopadhyay et al, 2010). The EMT-inducing effect of TGF-b is mediated in transformed hepatocytes by the induction of growth factors in stromal myofibroblasts, which themselves cause EMT (van Zijl et al, 2009). In the RAS-RAF pathway, extracellular signal-regulated kinase 2 (ERK2) would specifically be involved in EMT induction but not ERK1 (Shin et al, 2010).…”
Section: Cancer Cells S Floor Et Almentioning
confidence: 99%
“…Moreover, recent reports suggested an interaction between PDGF signaling and Wnt/b-catenin signaling (25)(26)(27). We evaluated Wnt/b-catenin signaling in Pdgf-c Tg mice and showed by IHC staining that b-catenin was overexpressed in the submembrane at week 48 (Fig.…”
Section: Peretinoin Inhibits Hepatic Angiogenesis In Pdgf-c Tg Micementioning
confidence: 99%
“…In HCC, the progression of malignant hepatocytes frequently depends on transforming growth factor (TGF)-beta provided by the stromal cells (fibroblasts, macrophages etc). This TGF-beta is one of the factors that can induce an Epithelial-to-Mesenchymal Transition (EMT) [80] . For different types of tumors it has been demonstrated that an EMT-switch is associated with a worse prognosis as seen in esophageal squamous cell carcinoom [81] , gastric cancer cells [82] bladder cancer [83] non-small cell lung cancer [84] and pancreas ductal adenomacarcinoma [85] .…”
Section: Hepatocarcinogenesis and Tumormicroenviromentmentioning
confidence: 99%